2022
DOI: 10.1371/journal.pone.0267277
|View full text |Cite
|
Sign up to set email alerts
|

Who is meeting the strengthening physical activity guidelines by definition: A cross-sectional study of 253 423 English adults?

Abstract: The current UK physical activity guidelines recommend that adults aged 19 to 65 years perform activity to strengthen muscle and bone a minimum of twice weekly. The number of adults meeting strengthening activity guidelines is lower than for aerobic activity, but estimates vary between studies partly due to differences in how muscle-strengthening activity is defined. We aimed to provide estimates for strengthening activity prevalence in English adults based on a nationally representative sample of n = 253,423 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…Therefore, our goal should not only be to treat the patient, but also to change his lifestyle to a more active one. Many works confirm that a small number of adults meet physical activity guidelines [23,24].…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, our goal should not only be to treat the patient, but also to change his lifestyle to a more active one. Many works confirm that a small number of adults meet physical activity guidelines [23,24].…”
Section: Discussionmentioning
confidence: 92%
“…After removing duplicates and screening titles, 67 studies were assessed for eligibility based on full text. A total of 21 studies were finally included in the present meta-analysis 8 9 21–39. The PRISMA flow diagram illustrating the number of studies excluded at each stage of the systematic review and meta-analysis is shown in figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…Studies were conducted in Australia,21 Austria,30 32 Bulgaria,26 Croatia,26 Cyprus,26 Czechia,26 Denmark,26 Estonia,26 Finland,22 26 France,26 Germany,25 26 Greece,26 Hungary,26 Iceland,26 Ireland,26 Italy,26 Latvia,26 Lithuania,26 Luxemburg,26 Malta,26 The Netherlands,26 31 Norway,26 Poland,26 Portugal,26 Romania,26 Slovakia,26 Slovenia,26 South Korea,24 33 36 Spain,26 Sweden,26 the UK26 and the USA 8 9 23 27 29 35 38 39. Sources of information included the National Nutrition and Physical Activity Survey,21 Regional Health and Well-being Study,22 US Behavioural Risk Factor Surveillance System surveys,23 27 Korea National Health and Nutritional Examination Survey,24 36 German Health Update Survey,25 European Health Interview Survey,26 National Youth Physical Activity and Nutrition Study,39 Youth Risk Behaviour Survey,9 Health Survey for England study,28 National Health and Nutrition Examination Survey,29 35 Austrian Health Interview Surveys,30 32 Dutch Health Survey/Lifestyle Monitor by Statistics Netherlands,31 National Health Insurance Service of South Korea,33 Active Lives Survey34 37 37 and the NHIS 8 38. Aerobic and MSA were self-reported in most studies, although one study29 directly measured aerobic physical activity through accelerometers.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 However, the majority of the population worldwide does not reach PA recommendations, especially when strengthening activities are considered. [4][5][6][7][8] PA can be practiced in many ways, including active transportation, work, gardening, housework, active forms of recreation, and sports, and can be promoted using a variety of strategies. 9,10 In addition to PA-friendly environments, 11 PA can be efficiently promoted in daily settings, such as health care systems, 12 schools, 13 and sport clubs.…”
mentioning
confidence: 99%